2016
DOI: 10.1016/j.techfore.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship capital types and economic growth: International evidence

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(99 citation statements)
references
References 72 publications
5
86
0
2
Order By: Relevance
“…They show that entrepreneurship facilitates knowledge spillovers, which conduct to enhance economic growth (Prieger et al, 2016). From this perspective, Audretsch and Keilbach (2004) introduced entrepreneurship capital into a standard Cobb-Douglas production function and found that the startups of entrepreneurship lead to greater economic growth across 327 West German regions over the period 1989-1992. In the same context, Urbano and Aparicio (2015) empirically examined the effect of three different types of entrepreneurship capital (overall total entrepreneurial activity (TEA), opportunity TEA, and necessity TEA) on economic growth using the neo-classical augmented…”
Section: (I) Economic Impact Of Entrepreneurship: Entrepreneurship Anmentioning
confidence: 99%
“…They show that entrepreneurship facilitates knowledge spillovers, which conduct to enhance economic growth (Prieger et al, 2016). From this perspective, Audretsch and Keilbach (2004) introduced entrepreneurship capital into a standard Cobb-Douglas production function and found that the startups of entrepreneurship lead to greater economic growth across 327 West German regions over the period 1989-1992. In the same context, Urbano and Aparicio (2015) empirically examined the effect of three different types of entrepreneurship capital (overall total entrepreneurial activity (TEA), opportunity TEA, and necessity TEA) on economic growth using the neo-classical augmented…”
Section: (I) Economic Impact Of Entrepreneurship: Entrepreneurship Anmentioning
confidence: 99%
“…Drawing on this, policies fostering any type of entrepreneurship could be harmful in the long-term, since some entrepreneurial activity does not contribute to social value creation . Although Urbano and Aparicio (2016) cannot conclude anything in terms of necessity entrepreneurship, they found that the entrepreneurial activity related to innovation and opportunity seeking had a longer impact on economic growth. Similarly, Acs et al (2012), Aparicio et al (2016a), Minniti and Lévesque (2010) and Wong et al (2005), among others, found that the entrepreneurial activity associated with innovation was positively related to economic growth.…”
Section: Policy Discussionmentioning
confidence: 95%
“…In this context, the entrepreneur is seen as the agent of change who can contribute toward progress and technology transformation through innovation (Teece 1986). Thus, entrepreneurial activity is a valid conduit for the establishment of new activities that promote economic performance and new jobs, as well as ensuring the well-being of society at regional and national levels (Acs et al 2012;Avlonitis and Salavou 2007;Beugelsdijk 2007;Busenitz et al 2003;Carlsson et al 2013;Díaz et al 2013;Feldman 2014;Ribeiro Soriano and Peris-Ortiz 2011;Urbano and Aparicio 2016;van Praag and Versloot 2007;Wennekers and Thurik 1999). Examining the factors that encourage innovative entrepreneurial activity has attracted the interest of academics and others in different fields and with different perspectives (Audretsch 2012;Shane and Venkataraman 2000;Thornton et al 2011;Veciana and Urbano 2008;Verheul et al 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to long-term economic growth, a strategy that appears associated with entrepreneurial motivation to do with the exploration and evaluation of significant opportunities. if not, then that should be done is the entrepreneurial activity must be motivated by the need to solve short-term problems, but has no effect on long-term economic growth [10]. of the above concept is clear that the employer in this case serves as an innovator in issuing new varieties and increase the amount of production effort, so it can increase the amount of sales of each business unit so that gradually the business activities will grow and will affect the labor market and on eventually will result in the economic development of a country.…”
Section: The Entrepreneur Innovation In Economic Developmentmentioning
confidence: 99%